Effect of isoprenaline on 85Sr accumulation in the myocardium of the adult rat - Ostádalová, I; Ostádal, B (Physiologia Bohemoslovaca, 1988)
The administration of a single dose of isoprenaline to adult male rats stimulated 85Sr uptake by their blood, liver and myocardium. Whereas the 85Sr concentration in the blood and liver rose by only 36% and 42% respectively, the increase in the various compartments of the heart was 5-7 times this value. This finding is also documented by the increase in the ratio of the 85Sr concentration in the heart and blood. The increase observed in 85Sr accumulation in the myocardium is comparable to the repeatedly described changes which occur in radioactive calcium after the administration of isoprenaline.
Keywords: srdce; isoprenalin; krysa rodu Rattus; Strontium; Isoproterenol; Myocardium; Male; Animals; Liver; Rats, Inbred Strains; myokard; mužské pohlaví; játra; inbrední kmeny potkanů; Heart; zvířata; stroncium; Rats